Living GenoChemetics by hyphenating synthetic biology and synthetic chemistry in vivo - Sunil V. Sharma (Nature Portfolio, 2017)
Coupling synthetic biology and chemical reactions in cells is a challenging task. The authors engineer bacteria capable of generating bromo-metabolites, develop a mild Suzuki-Miyaura cross-coupling reaction compatible with cell growth and carry out the cross-coupling chemistry in live cell cultures.